Immunomodulatory Strategies Directed Toward Tolerance of Vascularized Composite Allografts. Issue 8 (August 2015) - Madariaga, Maria Lucia L.; Shanmugarajah, Kumaran; Michel, Sebastian G.; Villani, Vincenzo; La Muraglia, Glenn M.; Torabi, Radbeh; Leonard, David A.; Randolph, Mark A.; Colvin, Robert B.; Yamada, Kazuhiko; Madsen, Joren C.; Cetrulo, Curtis L.; et al.
<x xml:space="preserve">Abstract</x> Background Achieving tolerance of vascularized composite allografts (VCAs) would improve the risk-to-benefit ratio in patients who undergo this life-enhancing, though not lifesaving, transplant. Kidney cotransplantation along with a short course of high-dose immunosuppression enables tolerance of heart allografts across a full major histocompatibility complex (MHC) mismatch. In this study, we investigated whether tolerance of VCAs across full MHC disparities could be achieved in animals already tolerant of heart and kidney allografts. Methods Miniature swine that were tolerant of heart and/or kidney allografts long term underwent transplantation of myocutaneous VCA across the same MHC barrier. Before VCA transplant, group 1 (n = 3) underwent class I–mismatched kidney transplantation; group 2 (n = 3) underwent 2 sequential class I–mismatched kidney transplantations; group 3 (n = 2) underwent haploidentical MHC-mismatched heart/kidney transplantation; and group 4 (n = 2) underwent full MHC-mismatched heart/kidney transplantation. Results All 3 animals in group 1 and 2 of 3 animals in group 2 showed skin rejection within 85 days; 1 animal in group 2 showed prolonged skin survival longer than 200 days. Animals in groups 3 and 4 showed skin rejection within 30 days and regained in vitro evidence of donor responsiveness. Conclusions This is the first preclinical study in which hearts, kidneys, and VCAs have been transplanted into the same recipient. Despite VCA rejection, tolerance of heart and kidney allografts was maintained. These results suggest that regulatory tolerance of skin is possible but not generally achieved by the same level of immunomodulation that is capable of inducing tolerance of heart and kidney allografts. Achieving tolerance of skin may require additional immunomodulatory therapies.